An external portable device for adaptive deep brain stimulation (aDBS) clinical research in advanced Parkinson's Disease. Issue 5 (May 2016) - Arlotti, Mattia; Rossi, Lorenzo; Rosa, Manuela; Marceglia, Sara; Priori, Alberto
Highlights: DBS limitations in treating PD patients might be overcome by closed-loop devices implementing adaptive stimulation protocols. We developed an external portable aDBS system prototype aimed to promote clinical investigations in Parkinson's Disease. We validated the aDBS system prototype. The aDBS system prototype successfully tracked the power changes induced by medication and stimulation by means of a real-time spectral analysis. Abstract: Compared to conventional deep brain stimulation (DBS) for patients with Parkinson's Disease (PD), the newer approach of adaptive DBS (aDBS), regulating stimulation on the basis of the patient's clinical state, promises to achieve better clinical outcomes, avoid adverse-effects and save time for tuning parameters. A remaining challenge before aDBS comes into practical use is to prove its feasibility and its effectiveness in larger groups of patients and in more ecological conditions. We developed an external portable aDBS system prototype designed for clinical testing in freely-moving PD patients with externalized DBS electrodes. From a single-channel bipolar artifact-free recording, it analyses local field potentials (LFPs), during ongoing DBS for tuning stimulation parameters, independent from the specific feedback algorithm implemented. We validated the aDBS system in vitro, by testing both its sensing and closed-loop stimulation capabilities, and then tested it in vivo, focusing on the sensing capabilities. By applying the aDBS system prototype in a patient with PD, we provided evidence that it can track levodopa and DBS-induced LFP spectral power changes among different patient's clinical states. Our system, intended for testing LFP-based feedback strategies for aDBS, should help understanding how and whether aDBS therapy works in PD and indicating future technical and clinical advances.